Gamification for teaching the Arabic language to non-native speakers: a systematic literature review - Almelhes, Sultan A. (Frontiers in Education, 2024)
Learning the Arabic language through gamified methods is beneficial, particularly for beginners. Gamification provides an enjoyable and challenging experience for the learners, motivating them to become committed and participate in the classroom activity. The students develop a more competitive spirit and anticipate their chances of achieving high scores for each game level and ranking high against fellow learners. Game elements like feedback and audio pronunciations assist in user engagement with the teacher and other learners. This systematic literature review critically synthesizes past literature to create an understanding of the application and effectiveness of gamified learning strategies for Arabic language learning. PRISMA technique was used for conducting systematic review and after final scrutiny, 15 articles was shortlisted for review. The findings suggested that gamification improves learner motivation, engagement and achievement in mastery of Arabic vocabulary and grammar among non-native speakers. The degree of motivation is influenced by the teacher's perception, attitude, enthusiasm and commitment to gamified learning strategies. The findings of this systematic review can help language instructing institutions to emphasize gamification for enhancing the motivation of learners and increasing their learning abilities. Moreover, it can be helpful for instructors of Arabic language, they can realize the importance of gamification in teaching Arabic to non-native speakers.